HIGH SCHOOL STUDENTS’ PERSPECTIVE ON USING DUNGEONS & DRAGONS FOR ENGLISH SPEAKING PRACTICE - Biyan Aji Kurniawan; Dias Andris Susanto; Laily Nur Affini (University of Kuningan, 2024)
This study explores the potential of using Dungeons & Dragons (D&D) as a media for teaching English speaking skills among high school students. The primary objective is to understand students' reactions and responses when D&D is incorporated into their English learning curriculum. Through a series of observations, questionnaire and Interview, students participated in D&D campaigns designed to stimulate verbal communication, critical thinking, and collaborative storytelling. The findings reveal that students exhibited increased engagement, and a positive attitude towards using this unconventional method for learning English. This research aims to shed light on the effectiveness and student perception of gamified learning tools in language education, offering insights for educators seeking innovative approaches to language instruction.